Mepacrine Blockade of Arachidonate-lnduced Washed Platelet Aggregation: Relationship to Mepacrine Inhibition of Platelet Cyclooxygenase - Raz, Amiram (Thrombosis and Haemostasis, 1983)
Mepacrine, in addition to its established antilipolytic activity, was also found to inhibit the conversion of 14C-arachidonic acid to 14C-thromboxane B2 in human washed platelets. In the concentration range of 3.33-33 μM, mepacrine exerted a dose dependent inhibition of arachidonate conversion to thromboxane B2 in parallel to inhibition of arachidonate-induced platelet aggregation. Mepacrine inhibition of thromboxane formation was not accompanied by a concomitant increase in other cyclooxygenase products. Furthermore, mepacrine did not affect platelet transformation of added prostaglandin H2 to thromboxane A2 and other products. These results indicate that mepacrine inhibits the cyclooxygenase enzyme and not thromboxane synthase. In washed platelets, mepacrine inhibition of arachidonic acid conversion to thromboxane A2 appears to be a major factor in the overall inhibitory effect of the compound on the combined process of arachidonate release from cellular phospholipids and its conversion to proaggregatory products.
Keywords: Mepacrine; Platelet aggregation; Arachidonic add; Cyclooxygenase